HUBUNGAN KREATIVITAS DENGAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN PENATAAN SANGGUL (UP STYLE) PADA SISWA KELAS XI SMK N 7 PADANG - Sari, Agnes Mai; Rahmiati, Rahmiati; Yanita, Merita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The type of the research is qualitative deskriptive research that is corelasional. The population of this study is the students of class XI majoring in hair beauty SMK N 7 Padang that has followed 45 (up style) seting. The sampling tecnique from this research is the total sampling of data collection is by using questionnaire by using skala which is tested the validity. Analysis tecnique of achievment level of respondent with formula percentage of tes requirements analysis by using normality and linieritas test while correlation coefficient analysis using person correlation product moment and for hypothesis test of t test. The results stated that the creativity of students included in the category was with the percentage 71% while the average of student learning outcemes os 73 which states still below KKM. KKM is determinated is 75. The result of correlation analysis obtained r value count of 0,685 with a strong relationship interpretation with a significance value 0,000 <0,05. Ha test accepted suggested to teachers to improve students creativity through efforts to use learning resources and learning strategies that build more and encourage student creativity .Keywords: Creativity, Learning Out Comes, Structuring (Up Style)